Three faces of justice: Competing ethical paradigms in forensic psychiatry - Adshead, Gwen (Legal and criminological psychology, 2014)
Respect for justice has traditionally been an essential principle of health care ethics. However, many bioethical accounts of justice focus only on distributive justice, and how resources for health care should be allocated. In this article, I will argue that the practice of forensic mental health care requires clinicians to engage with justice in three additional and different ways: justice as liberty and fairness; retributive justice and protection of the vulnerable; and justice as the promotion of virtue. I will argue that British forensic psychiatry favours retributive and protective justice; in contrast to a libertarian approach to forensic practice in the United States. I discuss how respect for justice as support for virtue complements therapeutic work with offenders, which aims at the development of pro-social character. I will conclude that without respect for justice as virtue, there is a danger that clinical forensic psychiatry risks doing harm to patients and bringing the profession into disrepute.